A behavioral view of family firm disclosures - YOSHIKAWA, Toru (Institutional Knowledge at Singapore Management University, 2016)
We investigate sources of heterogeneity in governance disclosures among publicly listed family firms. Disclosures are a strategic issue as families generally prefer discretion in decision-making. Drawing from the behavioral theory of the firm we theorize that family firms’ disclosures vary depending on perceived performance. Our study of listed family firms in Singapore suggests that firms with greater negative performance-aspiration gaps are associated with better disclosures, that disclosure types matter as well as family involvement in management. Our study suggests that behavioral theory offers a novel and more fine-grained explanation for family firm heterogeneity in governance disclosures.